Effect of application levels of guano of islands in increase of cocoa fruits - Parco-Quispe, Maximo (2022)
The experiment was carried out in two agricultural campaigns, due to problems of low productivity of organic cocoa cultivation in the Central Selva, with the objective of determining the optimal dose of application of island guano per plant, increasing cocoa productivity and economic income of the producers, the amounts applied per treatment were: T1 300 g, T2 400 g, T3 600 g, T4 800 g, T5 1000 g, and T6 without fertilizer. The applications were made in two moments: the first dose (50%) before the start of flowering in the month of October 2016 and the second during the fruit growth in the month of March 2017. In the second campaign 2017 and 2018 the same procedure was followed. The variables evaluated were: number of fruits per plant, weight of ripe ears, number of almonds per ear, weight of dry almonds per ear and dry almond yield / ha. The application of island guano was made by making small holes in a half moon in the upper part 50 cm away from the stem of the plant, as a result an increase was found in the number of fruits per plant, weight of ripe pods, number of almonds per ear and weight of dry almond. In conclusion, the doses that influenced greater cocoa productivity were T4 800 g and T5 1000 g per plant, it was also observed that in the first campaign the increase was greater than the second campaign.